Levels of heavy and essential trace metals and their correlation with antioxidant and health status in individuals occupationally exposed to municipal solid wastes - Odewabi, Adesina O; Ekor, Martins (Toxicology and industrial health, 2017)
Recent studies have indicated an increased incidence of toxic neuropathies among waste management workers (WMW) possibly linked to increased detection of heavy metals in municipal solid wastes. The present study evaluated serum levels of some heavy and essential trace metals in relation to oxidant/antioxidant status of WMW. One hundred and twenty-six WMW and 84 non-WMW (control) were recruited. Metal/element concentration was measured by atomic absorption spectrophotometry and oxidant/antioxidant markers were determined using standard procedures. The WMW exhibited significantly ( p < 0.001) decreased ferric reducing ability of plasma (FRAP) and higher levels of ceruloplasmin (Cp) and malondialdehyde. Iron (Fe) and copper (Cu) levels were significantly lower ( p < 0.05) and higher ( p < 0.001), respectively in WMW when compared with control while levels of other trace elements were not significantly different between these groups. Lead (Pb) and chromium levels were significantly higher ( p < 0.001 and p < 0.05, respectively) in WMW while mercury levels were comparable with those of control subjects. In WMW, Cp ( r = -0.182; p > 0.05) and FRAP ( r = 0.277; p < 0.05) negatively and positively correlated with Pb, respectively, while a positive correlation was observed between zinc ( r = 0.230; p < 0.05) and Pb and between Cu ( r = 0.541; p > 0.001) and Fe. Overall, the decreased antioxidant capacity and increased oxidative stress observed in WMW in this study may be related to their blood levels of heavy and essential trace metals. Conscious efforts are required, therefore, to reduce risk and protect WMW from toxic neuropathies and other adverse health consequences of occupational exposure.